Emerging tri‐s‐triazine‐based graphitic carbon nitride: A potential signal‐transducing nanostructured material for sensor applications. Issue 4 (30th December 2020) - Chouhan, Raghuraj Singh; Jerman, Ivan; Heath, David; Bohm, Sivasambu; Gandhi, Sonu; Sadhu, Veera; Baker, Syed; Horvat, Milena
Abstract: Today, tris‐s‐triazine based graphitic carbon nitride (g‐C3 N4 ) is a new research hot topic. It has a unique electronic band structure, high physicochemical stability, large surface area, and is "earth‐abundant." These and other properties have made it a highly researched material especially for visible light photocatalysis and photodegradation applications and as the starting material from which to develop novel electrochemical sensing platforms. In this review, the state‐of‐the‐art technologies utilizing tris‐s‐triazine graphitic carbon nitride as a tailorable signal‐transducing nanostructured material for sensing applications is presented in detail. Initially, the electronic structure of g‐C3 N4, morphologies, doping, heterojunctions, its combination with other carbon materials, and defect formation, is described, which is followed by a discussion on its role in electrochemiluminescence, photoelectrochemical, fluorescence sensors and gas sensors as a signal transducer with appropriate examples. This review concludes with a discussion summarizing state‐of‐the‐art and both future perspectives and challenges at the cutting edge of this research. Abstract : The unique properties of nanostructured g‐C3 N4 that include exceptional electronic band structure, excellent physicochemical stability, large specific surface area, and beneficial electronic, optical, thermal, and mechanical properties, and the ability to tailor its morphology, makes g‐C3 N4 a promising signal‐transducing material for cost‐effective and reliable sensors. This review paper discusses the current development of g‐C3 N4 based sensors in different applications.